Reimagining Malcolm X: Street Thinker Versus Homo Academicus By Seyed Javad Miri (Lanham, MD: University Press of America, 2016. 84 pages.) (American Journal of Islam and Society, 2016)
At 84-pages, Reimagining Malcolm X: Street Thinker Versus Homo Academicusby Seyed Javad Miri is more of a booklet than a book. In fact, like mostof the 40 books on sociology and religion published by this scholar, many ofwhich are self-published or released by subsidy publishers, it falls into thatawkward category between an essay that is too long and a book that is tooshort. Considering the fact that most university and independent academicpresses place profit and marketability before contribution to scholarship inthe field, the fact that ambitious and prolific academics seek to be proactiveand find alternate modes of sharing their scholarship should be commended.Consequently, scholars working in the field of sociology and religion shouldbe grateful to both Miri and the University Press of America for making thiswork on Malcolm X available to readers and researchers.Reimagining Malcolm X examines the significance of el-Hajj Malik el-Shabazz as a social theorist by analyzing his views on race, academia, philosophy,and politics. The work is divided into four chapters: “Novel Strategiesof Interpretation,” “Undisciplinary Fields of Knowledge,” “Violence, Religion,and Extremism,” and “The Epic of America.”In chapter 1, Miri points out that “Malcolm X has not been appropriatedwithin the body of academic social sciences as he should have been” (p. 9).This is both obvious and intentional. It is heartening, however, to see thatinterest in Malcolm’s thoughts has extended to certain segments of Iranianacademia. As the author reveals, however, some Iranian scholars are reticentto see the value of Malcolmian theories and concepts (p. xi). Despite all ofits revolutionary rhetoric, the Islamic Republic of Iran has shown little interestin el-Hajj Malik el-Shabazz. On the contrary, it has preferred to invitehis nemesis Louis Farrakhan, a man who admits that he created the conditionsthat lead to Malcolm’s assassination, to preach at the seminary in Qum.Considering that the Iranian regime considers itself the bastion of Shi‘iteorthodoxy and cracks down on both political critics and practitioners oftaṣawwuf (‘irfān or Sufism), it is ironic that its leaders have promoted a manwho believes that W. D. Fard was the incarnation of Allah and that ElijahMuhammad, as opposed to Muhammad ibn ‘Abd Allah, was Allah’s final ...